2019
DOI: 10.1097/ajp.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Parents Reliably Identify Pain Dismissal by Pediatric Providers

Abstract: Objectives: Approximately 40% of children and adolescents with chronic pain report at least 1 dismissal experience, citing medical providers and parents as the primary and most distressing dismissers. Previous research indicates sex differences in pain dismissal experience and observer pain perception. This study examined parental reactions to dismissive provider-child scenarios and the influence of provider and patient sex on perceptions. Methods: Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A core tenet of FCC, high-quality communication in which one feels that their concerns are understood is an important correlate of parent satisfaction with health care (Beckett et al, 2009). Prior research on provider dismissal of patient concerns has focused on specific concern types, such as adolescent and emerging adult experiences of pain dismissal (Defenderfer et al, 2018;Igler et al, 2017Igler et al, , 2020Lang et al, 2018) and parents' developmental (Johnson et al, 2020) and mental health (Pidano, 2020;Pidano et al, 2017) concerns. The present study observed that a minority of parents reported at least one lifetime instance of pediatric concern dismissal, which was often associated with distress and dissatisfaction with the health care system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A core tenet of FCC, high-quality communication in which one feels that their concerns are understood is an important correlate of parent satisfaction with health care (Beckett et al, 2009). Prior research on provider dismissal of patient concerns has focused on specific concern types, such as adolescent and emerging adult experiences of pain dismissal (Defenderfer et al, 2018;Igler et al, 2017Igler et al, , 2020Lang et al, 2018) and parents' developmental (Johnson et al, 2020) and mental health (Pidano, 2020;Pidano et al, 2017) concerns. The present study observed that a minority of parents reported at least one lifetime instance of pediatric concern dismissal, which was often associated with distress and dissatisfaction with the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond surveys, future concern dismissal research should incorporate perspectives of providers and pediatric patients. This may include using recordings of pediatric medical encounters (Callery & Milnes, 2012;Giambra et al, 2018;Wissow et al, 1994Wissow et al, , 2005 or written vignettes (Igler et al, 2020;Lang et al, 2018), to allow for more objective study of concern dismissal. Prior vignette studies of pain dismissal experiences may also serve as models for more detailed explorations (e.g., Igler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who report symptoms are assumed to make the symptoms up or have a mental disorder. These patients are often thought to be demanding and dismissed by physicians [ 15 , 16 ]. Families carry theses same beliefs.…”
Section: Gut Symptoms Are Either In Your Gut or Your Mindmentioning
confidence: 99%
“…Youth with chronic pain, and their families, experience this diagnostic uncertainty in the context of repeated negative medical findings ( Neville et al, 2019 ), alongside providers who may not feel confident in their management of pediatric chronic pain ( Neville et al, 2020 ). Many parents have also indicated feeling that their child’s pain symptoms are often dismissed by pediatric providers ( Igler et al, 2020 ). The invisibility of chronic pain symptoms has led to adolescents with chronic pain experiencing pain-related stigma, specifically in the form of others indicating that they do not believe their pain is “real,” and/or believing that the person is making up their symptoms ( Wakefield et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%